2000
DOI: 10.1007/s10434-000-0120-z
|View full text |Cite
|
Sign up to set email alerts
|

Technical Details of Sentinel Lymph Node Mapping in Colorectal Cancer and Its Impact on Staging

Abstract: SLN mapping can be performed easily in colorectal cancer patients, with an accuracy of more than 95%. The identification of submicroscopic lymph node metastases by this technique may have upstaged these patients (18%) from stage I/II to stage III disease, who may then benefit from further adjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
146
0
13

Year Published

2002
2002
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(163 citation statements)
references
References 9 publications
4
146
0
13
Order By: Relevance
“…Initial studies reported encouraging results, with a 98% SLN identification rate and a 96% accuracy rate for SLNs as an indicator of the regional lymph node status. [13][14][15] We have been unable to duplicate those initial results. In our previous study, we reported an FN rate of 38%.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies reported encouraging results, with a 98% SLN identification rate and a 96% accuracy rate for SLNs as an indicator of the regional lymph node status. [13][14][15] We have been unable to duplicate those initial results. In our previous study, we reported an FN rate of 38%.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node dissection areas can be accurately assessed by SNNS in patients with breast cancer and malignant melanoma (Veronesi et al, 1997;Edwards et al, 1998). The SN concept has recently been applied to gastrointestinal tract cancers including gastric cancers (Saha et al, 2000;Aikou et al, 2001;Uenosono et al, 2003), but its clinical application remains controversial. An assured diagnosis of lymph node micrometastasis determined by RT -PCR is essential when performing SNNS, since the clinical significance of lymph node micrometastasis is also contentious (Ishida et al, 1997).…”
Section: Lymphatic Invasion and Micrometastasis In Gastric Cancer T Amentioning
confidence: 99%
“…The key causative factor of recurrent gastric cancer is lymph node micrometastasis. The sentinel node (SN) concept has recently been applied to gastrointestinal tract cancers including gastric cancer (Saha et al, 2000;Aikou et al, 2001;Uenosono et al, 2003). During sentinel node navigation surgery (SNNS), lymph node micrometastasis cannot be disregarded.…”
mentioning
confidence: 99%
“…Many reports of SLN biopsy in CRC are emerging [60][61][62][63][64][65][66][67][68]. These studies vary from small single-institution reviews to prospective multi-institutional studies.…”
Section: Colonmentioning
confidence: 99%